Neurobiological Processes of Risk and Resilience in Adolescence: Implications for Policy and Prevention Science. Issue 1 (March 2014) - Busso, Daniel S.
ABSTRACT This article focuses on the concepts of risk and resilience and their potential to inform clinical interventions, school‐based prevention programs, and social policies. Research suggests that childhood adversity can trigger a cascade of psychological and neurobiological events that can lead to mental disorders in later life. Yet little is known about how these processes manifest in adolescence, a developmental window that is typically associated with an elevated risk for psychopathology and represents a period of neurological growth and reorganization that is second only to early childhood. A better understanding of adolescent brain development may provide an empirical grounding to improve the focus and timing of interventions, particularly those that target self‐regulation, meta‐cognition, and social supports. Finally, opportunities and challenges that emerge when bridging neuroscience and prevention science are discussed.